OQÍWShÍLARDA KOMMUNIKATIVLIK PROCESTIŃ DIDAKTIKALÍQ ÓZGEShELIKLERI HÁM ONDA QOLLANÍLATUǴÍN DIALOG TEXNOLOGIYASÍNÍŃ QURAMÍ HÁM XARAKTERI - Utemuratov, B.K. (SCIENCE and SOCIETY, 2025)
The article discusses the stages of developing students’ communicative competence, its development, speech development, the selection of learning resources that serve to expand their cognitive abilities, and ensuring the effectiveness of adequately applying methods and techniques for organizing the communicative learning process. The process of applying communication technologies based on dialogue encompasses a number of methods and techniques.